Sectoral allocations of domestic credit and their effects on economic growth in Ethiopia - Tesfamlak Gizaw; Zerihun Getachew; Malebo Mancha (Cogent Economics & Finance, 2024)
The optimal allocation of financial resources by well-established financial systems is crucial for fostering economic growth. Nevertheless, due to imperfections in real-world settings, financial systems inadvertently distribute credit to unproductive sectors, resulting in inefficiencies in economic performance. Thus, this study aims to investigate the sectoral allocations of credit and how, in turn, such credit allocations affect the performance of each economic sector, from 1991 to 2022. To this effect, it employed the Cross-Section Augmented Error Correction (CS-ECM) model, and this model has a PMG estimation technique; hence, heterogeneous (short-run) and homogeneous (long-run) coefficients are computed as a result. The descriptive results show that domestic credits that are allocated to agriculture, industry, services, and the private and public sectors are not only small but also misallocated to inefficient sectors. Similarly, the econometrics results indicate that credits given to the public and industry sectors have a negative effect on output growth in the short term, while credits distributed to the agricultural, service, and private sectors have a small but positive effect on growth. Besides, the long-term results show that the overall credit allocation to the economy has negative effects on growth, indicating credit misallocation has unfavorable long-term effects compared to short-term effects. Financial policies and strategies should therefore be designed to welcome foreign banks as well as capacitate the existing domestic financial institutions so that substantial financial resources can be mobilized, both from the external and internal economies, and distributed in such a way as to 'give more credit to an efficient sector'. Since credit is essential to many business and economic endeavors, it ought to be distributed to the most prosperous industries, which make significant contributions to both economic expansion and improved living standards. Nonetheless, the majority of developing nations experience inefficiencies in their economic performance as a result of financial institutions lending to less productive economic sectors. This study also looks into the sectoral distribution of credit and how each Ethiopian economic sector performed from 1991 and 2022 as a result of these credit distributions. And the study's findings first showed that there is a misallocation of credit to less productive sectors in addition to financial institutions' inadequate lending to each industry. Second, it showed that the misallocation is the reason behind the negligible contributions of industry and the public sector to economic growth, as well as the little contributions of services, agriculture, and the private sector. As a result, these findings provide pertinent information to enterprises, sectors, and financial institutions. It also provides information for researchers who need to do more study in relevant fields. The results of this study are also very beneficial to policymakers, who should create proper financial and economic policies.
Keywords: 330; Domestic credit; Sectoralpanel; Allocation efficiencyCS-ECM; Economic growth